(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
We studied the dynamics of hepatocyte proliferation after liver cirrhosis in rats, assessed the ratio of cell proliferation and cell death processes against the background of transforming growth factor β (TGF-β). Morphological changes in the liver in experimental cirrhosis were studied to assess the degree of fibrotic changes, the nature of hepatocyte damage and the state of the microcirculatory bed, the effect of TGF-β on regenerative processes in the liver by analyzing its effect on hepatocyte proliferation, activation of stellate cells and changes in the structure of the liver parenchyma.